Amphiphilic Functionalized Oligomers: A Promising Strategy for the Postfabrication Functionalization of Liposomes. Issue 22 (5th October 2020) - Wölk, Christian; Nawaz, Hafiz Awais; Maqsood, Iram; Strati, Fabio; Brezesinski, Gerald; Hause, Gerd; Schulz‐Siegmund, Michaela; Hacker, Michael C.
Abstract: Liposomes are promising drug carriers already used in clinical practice, but feasible methods for surface modifications are needed to enhance the application spectrum. This work describes the establishment of the first representative of amphiphilic functionalized oligomers as universal tool for the tuning of liposome characteristics based on a flexible building block strategy. The oligomer binds to liposomes composed of different lipids and modifies the surface characteristics. The charge of neutrally and even negatively charged liposomes is switched to a positive surface charge by grafting liposomes with the novel oligomer to create hybrid vesicles while integrity and structure of liposomes is not affected. The role of the alkyl chain anchors of the oligomer as driving force for formation of hybrid vesicles is demonstrated. The oligomer modification of liposomes is utilized to enhance the biological behavior of the vesicles demonstrated by an enhanced uptake in fibroblasts. Abstract : Amphiphilic functionalized oligomers (AFO) are customized oligomers with pendent chemical groups of widely adjustable functionality and alkyl anchors which are designed to decorate the surface of liposomes. This postfabrication modification can be used to control biocamouflaging, drug targeting, or to create theranostics. This proof‐of‐concept work uses a cationic AFO to induce a charge switch of liposomes and improve their cellular uptake.